A evolução da química brasileira Evolution of chemical research in Brazil - Peter Rudolf Seidl (Química Nova, 1997)
The recent evolution of chemical research in Brazil is analyzed. Progress has been substantial according to principal indicators. The contributions of the Brazilian Chemical Society are pointed out.